Experimental investigation on the unsteady pressure pulsation of reactor coolant pumps with non-uniform inflow. (December 2017) - Long, Yun; Wang, Dezhong; Yin, Junlian; Hu, Yaoyu
Highlights: The unsteady flow in reactor coolant pump with non-uniform inflow was investigated by experiment method. Influences of non-uniform inflow on flow structure and performance pump are analysed. Pressure pulsation signals are analysed by FFT and RMS method. Influences of rotating speed on pressure pulsation with non-uniform inflow are analysed. Abstract: In the third generation pressurized water reactor, the channel head of the steam-generator is directly connected with the reactor coolant pump. Non-uniform suction flow is generated at the inlet of the reactor coolant pump. But this situation has not been considered during the actual reactor system design process, because the pump is designed with uniform inflow. It is very necessary to conduct the research of the unsteady flow of the pump with non-uniform inflow by experiment method. Pressure pulsation signals measured from the seven sensors on the pump casing and outlet pipe are analysed by FFT and RMS method. From numerical simulation results, non-uniform inflow has a great effect on the flow structures in the pump. Pressure pulsation characteristics, both discrete peaks and RMS values, are easily affected by different operating conditions and measuring positions. Pressure amplitudes at f RPF (Rotor passing frequency) and f SPF (Stator passing frequency) decreases when the flow rate increases, but pressure amplitudes at f R exhibit the contrary trend. It is found that pressure amplitudes of RMS value and f RPF increase when the rotating speed increases. Nonlinear components of the frequency at the outlet could be identified easily, and more detailed analysis of the flow field need be carried out in the future. Finally, it is expected that the present work will provide a good reference for the pump design with non-uniform inflow.